MUSIC QUOTATION IN CONTEMPORARY NON-ACADEMIC ART: ASPECTS OF GENRE AND STYLE TRANSFORMATION - ARTEMENKO, Violetta (Studia Universitatis Babes-Bolyai Musica, 2023)
The problematic field of the article focuses on aspects of genre and style transformation of well-known musical content that is recognizable and stylistically significant. In contemporary non-academic art, the established semantics of the original source is subject to change under the influence of a new creative rethinking, the possibilities of which are only increasing in the context of the technologies of the twenty-first century. These possibilities are embodied in various visual formats: from direct citation to borrowing or processing with its variations. The relevance of this topic lies in the need to study the phenomenon of citation as such, as well as to research and systematize other means of genre and style transformation of musical material. The direct object of the study is mostly music of the so-called “light” genres, music of mass culture, due to more mobile, transparent and visual observation opportunities. The author offers a self-made classification of possible methods of borrowing someone else’s text as a means of compositional technique, as well as of individual genres: cover, remake, borrowing, allusion, sampling. In the context of the study of the phenomenon of “musical text”, the peculiarities of realization and perception of the artistic and integral result are traced. As a result, several types of citation that have become widespread in contemporary music are distinguished.